Istinbath Hukum Alauddin Al-Kasani Al-Hanafi Tentang Saksi Fasiq Dalam Pernikahan - Nurhadi, Nurhadi (Istinbath : Jurnal Hukum, 2020)
The implementation of marriage between one of the conditions of marriage is the existence of two witnesses, but to appoint a witness, it cannot be done carelessly such as appointing an evil witness. According to majority scholars, it is illegal to marry under an evil witness because that person is not a just person. Imam 'AlaUddin is of the opinion that it is legal to marry under an unfavorable witness for the following reasons: first, the Law of Ashal; Marriage will not take place if there are no witnesses, but in this case the nature of justice is not necessary but the aim is only to inform the public. Second, the Law of Intellect (ra'yun); Whereas if a poor person comes from the local population / area then he / she legally becomes a witness of marriage. Third, marriages occur in various places, both in villages and in remote areas, if only to find out firsthand whether a witness is fair or not, it will be burdensome and troublesome. Therefore, it is enough to look at the witness's general assessment, without having to know the details whether he or she has ever committed a major sin or not. Imam 'Alauddin took legal sources from the Koran, Hadith, and Istihsan. Based on this method, the ijtihad used by the imam 'Alauddin is a istihsan.